Robust humoral and cellular recall responses to AZD1222 attenuate breakthrough SARS-CoV-2 infection compared to unvaccinated - Maaske, Jill; Sproule, Stephanie; Falsey, Ann R.; Sobieszczyk, Magdalena E.; Luetkemeyer, Anne F.; Paulsen, Grant C.; Riddler, Sharon A.; Robb, Merlin L.; Rolle, Charlotte-Paige; Sha, Beverly E.; Tong, Tina; Ahani, Bahar; et al. (Frontiers in Immunology, 2023)
Background: Breakthrough severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in coronavirus disease 2019 (COVID-19) vaccinees typically produces milder disease than infection in unvaccinated individuals. Methods: To explore disease attenuation, we examined COVID-19 symptom burden and immuno-virologic responses to symptomatic SARS-CoV-2 infection in participants (AZD1222: n=177/17,617; placebo: n=203/8,528) from a 2:1 randomized, placebo-controlled, phase 3 study of two-dose primary series AZD1222 (ChAdOx1 nCoV-19) vaccination (NCT04516746). Results: We observed that AZD1222 vaccinees had an overall lower incidence and shorter duration of COVID-19 symptoms compared with placebo recipients, as well as lower SARS-CoV-2 viral loads and a shorter median duration of viral shedding in saliva. Vaccinees demonstrated a robust antibody recall response versus placebo recipients with low-to-moderate inverse correlations with virologic endpoints. Vaccinees also demonstrated an enriched polyfunctional spike-specific Th-1-biased CD4+ and CD8+ T-cell response that was associated with strong inverse correlations with virologic endpoints. Conclusion: Robust immune responses following AZD1222 vaccination attenuate COVID-19 disease severity and restrict SARS-CoV-2 transmission potential by reducing viral loads and the duration of viral shedding in saliva. Collectively, these analyses underscore the essential role of vaccination in mitigating the COVID-19 pandemic.